2014
DOI: 10.4238/2014.july.25.6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of seawater immersion-complicated open-knee joint fracture

Abstract: ABSTRACT. The current study aimed to select suitable remedies for seawater immersion-complicated open-knee joint fracture by exploring the effects of different treatment methods. Forty adult rabbits weighing 2.20 ± 0.25 kg were divided equally into internal fracture fixation group (A), seawater-immersed group with primary internal fixation (B), seawater-immersed group with secondary internal fixation (C), and seawater-immersed group with external fixation (D), using the randomdigit table method. Open-femoral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The marine industry has been developing in recent years, and marine workers are prone to various open injuries [26]. Several previous studies have reported that SW immersion causes large amounts of inflammatory factors, such as IL-8, TNF, and NO, to be released from the injured area, causing multiple organ damage in the body and increasing the probability of disseminated intravascular coagulation, which ultimately leads to an increase in mortality [4,[27][28][29][30][31]. However, the effects of SW immersion on wound repair of full-thickness skin defects and its mechanism have not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The marine industry has been developing in recent years, and marine workers are prone to various open injuries [26]. Several previous studies have reported that SW immersion causes large amounts of inflammatory factors, such as IL-8, TNF, and NO, to be released from the injured area, causing multiple organ damage in the body and increasing the probability of disseminated intravascular coagulation, which ultimately leads to an increase in mortality [4,[27][28][29][30][31]. However, the effects of SW immersion on wound repair of full-thickness skin defects and its mechanism have not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Highly permeable alkaline seawater causes an increased local osmolarity of the open abdominal cavity, intracellular dehydration, and tissue space edema. These states directly stimulate histiocytes to release inflammatory mediators such as IL-8, TNF- α , and TGF- β and aggravate the hemorrhage of small vessels in injured tissues [5]. A large number of pathogenic bacteria and toxins in the seawater can enter the blood circulation through the peritoneum, resulting in systemic diseases such as infection, shock, and MOF [6].…”
Section: Discussionmentioning
confidence: 99%